Exploring Ethnomathematics at the Islamic Center Mosque in Lhokseumawe as a Learning Resource for Arithmetic Sequences and Series in Junior High School - Rohantizani Rohantizani; Nuraina Nuraina; Mursalin Mursalin; Eri Saputra; Suwanto Suwanto; Rahmi Hayati (SAINTIS Publishing, 2026)
This study aims to explore the ethnomathematical potential embedded in the architecture of the Islamic Center Mosque in Lhokseumawe as a learning resource for teaching arithmetic sequences and series at junior secondary school level. The research adopts a qualitative approach employing an exploratory case study design. Data were collected through systematic architectural observations, visual documentation, semi-structured interviews with building managers and mathematics teachers, and numerical analysis of recurring structural patterns. The findings reveal that the arrangement of columns, arches, dome ornaments, and floor tile configurations exhibits numerical regularities that can be modelled using arithmetic sequences and series. The uniform spacing between columns reflects the concept of a common difference in arithmetic sequences, while the layered dome ornamentation illustrates the relationship between the nth term and the sum of the first n terms in an arithmetic series. These results demonstrate that mosque architecture embodies not only aesthetic and religious values but also structured mathematical principles relevant to classroom instruction. Integrating cultural context into mathematics learning enhances conceptual understanding, promotes student engagement, and increases the meaningfulness of abstract mathematical concepts. Therefore, the ethnomathematical exploration of mosque architecture offers a pedagogically sound and contextually relevant strategy for teaching arithmetic sequences and series in junior secondary education.